Preferences for on-demand/intermittent/event-driven and long-acting injectable (LAI) HIV pre-exposure prophylaxis (PrEP) among HIV-negative Black gay, bisexual, and other sexual minority men in the United States: A qualitative study - Adedotun Ogunbajo; Alexa Euceda; Raven Ekundayo; Jamil Smith; Temitope Oke; DeMarc Hickson (PLoS ONE, 2025)
Background Black sexual minority men (SMM) are disproportionately affected by HIV. Pre-exposure prophylaxis (PrEP) is a medication that reduces HIV acquisition. There is a gap in our understanding of the acceptability of and preference for on-demand and long-acting injectable (LAI)-PrEP among PrEP-eligible Black SMM. This study aimed to explore preference for on-demand and LAI-PrEP and reasons for those preferences among HIV-negative Black SMM of different PrEP use profiles (current PrEP users, current non-PrEP users, and PrEP discontinuers). Methods Between March 2022 and April 2023, we conducted 17 focus group discussions (FGDs) with a total of 58 HIV-negative (current PrEP users, non-PrEP users, and PrEP discontinuers) Black SMM residing in the Washington D.C. metropolitan area. We explored acceptability and interest in on-demand and LAI-PrEP and anticipated barriers and facilitators to uptake. Results Two key themes emerged around interest and preferences for on-demand PrEP and LAI-PrEP: 1) lack of interest in on-demand PrEP, and 2) high acceptability of LAI-PrEP. The reasons for lack of interest in on-demand PrEP were: 1) inability to accurately anticipate and plan for sexual activity in advance, 2) uncertainty about effectiveness of on-demand PrEP, and 3) potential for unnecessary medication use, especially when anticipated sexual activity doesn’t occur. Most participants finding LAI-PrEP to be highly acceptable can be attributable to: 1) LAI-PrEP being convenient, and 2) LAI-PrEP being a potential solution to suboptimal adherence to daily oral PrEP due to forgetfulness. Discussion While daily oral PrEP is the most utilized PrEP modality, some SMM—who might not be acceptable to oral PrEP—are capable of accurately identifying specific periods and circumstances for HIV infection. It is important that healthcare providers present on-demand PrEP as an option to individuals who fall into these categories. Programs to increase awareness and knowledge of LAI-PrEP among Black SMM and HCP that serve them are needed. Additionally, it is imperative that HCP who provide PrEP services receive proper training on the administration of LAI-PrEP and that there is dedicated staff to help clients navigate the insurance coverage process.